Presidential Threshold Dalam Memperkuat Sistem Pemerintahan Presidensial Berbasis Negara Hukum Pancasila - Dewanto, Wishnu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Through this study, the author actually presents a perspective related to the presidential threshold as a reinforcement of the presidential government system based on the Pancasila rule of law. The interesting side of this paper is whether the presidential threshold really curbs people's sovereignty or vice versa through the presidential threshold it actually creates a strong government that is directly elected by the people is people's sovereignty. This makes a strong dichotomy or the pros and cons of the 2 views. However, we need to emphasize whether the presidential threshold or not using it must still be within the framework of the Pancasila legal state. Where the rule of law in the Republic of Indonesia is based on the ideology and values of Pancasila as the basis of the state and the source of all sources of law. The process of people's sovereignty which is realized through direct presidential elections is very basic but no less important in overseeing the results of the people's sovereignty which is mandated by the President-elect to be able to carry out the running of the government in accordance with the 1945 Constitution of the Republic of Indonesia in realizing social justice for all Indonesian people. For this reason, the presidential threshold is very relevant as an effective way to strengthen the presidential government system.